Comorbidities of diabetes and hypertension in Vietnam: current burden, trends over time, and correlated factors - Thi Hoang Lan Vu; Thi Tu Quyen Bui; Quoc Bao Tran; Quynh Nga Pham; Duc Truong Lai; Tu Hoang Le; Van Minh Hoang (BMC, 2023)
Abstract Background Vietnam conducted the national Noncommunicable Disease Risk-Factor Surveillance (STEPs) surveys in the years 2010, 2015, and 2021. This study aims to use STEPs data to assess the burden of comorbidity between diabetes and hypertension, analyze trends over time, and identify factors associated with this comorbidity. Methods The study extracted data for the population aged 25-64 years old from three STEPs surveys. Survey weight was used for all estimations of prevalence and 95% CI. Correlated factors with comorbidity were examined by a multivariate logistics model. Results The prevalence of comorbidity in 2021 was about 3.92% among Vietnamese people aged 25-64. In the last 10 years, this prevalence has increased more than 8 times (from 0.44% to 3.92%). Sub-populations demonstrating the most significant changes included the male population, people living in urban areas, and older people. Significant factors correlated with comorbidity included demographic factors, body mass index (BMI), and clustering of 4 noncommunicable diseases (NCDs) behavioral risk factors (OR = 3.48, p < 0.05). Conclusion The high comorbidity between hypertension and diabetes underscores the imperative for integrated treatment and management approaches in Vietnam. Coordinated care is essential for addressing the complex interplay between these two prevalent conditions.